Nutrisi Antenatal Sebagai Pilar Utama Pencegahan Stunting Melalui Edukasi Ibu Hamil - Yanti, SST., M.Keb, Linda; Surtiningsih, Surtiningsih; Sekarini, Ni Nyoman Ayu Desy (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Stunting is a global health problem, including in Indonesia, caused by chronic malnutrition, recurrent infections, and inadequate stimulation during the first 1,000 days of life. Although the prevalence of stunting in Indonesia decreased from 24.4% in 2021 to 21.6% in 2022, it remains far from the national target of 14% by 2024. In Banyumas Regency, the prevalence has fluctuated, declining from 21.6% in 2021 to 16.6% in 2022, but rising again to 20.9% in 2023. The main contributing factors include limited maternal knowledge about optimal nutrition, low family income, and persistent pregnancy-related myths. The identified problem was the high prevalence of stunting and the absence of sufficient socialization or education programs for pregnant women regarding stunting prevention. The aim of this activity was to improve pregnant women’s knowledge about stunting prevention through the optimization of nutritional intake during pregnancy. The methods included the measurement of pre-pregnancy Body Mass Index (BMI), administration of a pretest questionnaire, delivery of health education on antenatal nutrition, stunting and its prevention, interactive discussions, and a posttest for evaluation. The program was attended by 28 pregnant women in Tamansari Village, Karanglewas District, Banyumas Regency. The results showed that 46.42% of participants had an underweight pre-pregnancy BMI. At baseline, most participants (82.14%) were categorized as having low knowledge, with an average score of 46.43. After the intervention, knowledge improved significantly, with 71.42% of participants categorized as having good knowledge, and the mean score increased to 79.64. In conclusion, antenatal nutrition education was proven effective in improving pregnant women’s knowledge and should be implemented continuously to support stunting prevention efforts from the early stages of pregnancy.